Design and fabrication of mechanically strong nano-matrices of linseed oil based polyesteramide blends - Killi, Naresh; Dhakare, Runali Arjun; Singam, Amarnath; Lokanadham, Metta; Chitikeshi, Harshavardhan; Gundloori, Rathna Venkata Naga (Medchemcomm, 2016)
New nanomaterials of bio-origin with improved mechanical properties are in demand for biomedical application. Therefore, we propose to design and fabricate bioactive nano-matrices with good mechanical strength using polyesteramides derived from linseed oil. Polyesteramide was synthesized from linseed oil and blended with poly(L-lactide) and human serum albumin to enhance the mechanical strength, biodegradation, biocompatibility and hydrophilicity. The various blend solutions with and without drugs (triclosan and metronidazole) were electrospun into non-woven nano-matrices. The morphology of the nano-matrices represented smooth and fine nanofibers with the diameter ranging from 300 to 400 nm. Drug binding efficiency, cytotoxicity, hydrophilicity, thermal and mechanical studies indicated their suitability as biomaterials. To demonstrate their utility, the drug release kinetics and antibacterial properties were evaluated. The metronidazole loaded nano-matrices showed drug release up to 8 h, beyond which no release was observed until 72 h. Antibacterial studies were done using the drugs triclosan and metronidazole. The antibacterial activity of the drug loaded nanofiber mats increased with the increase in drug concentration. The uniqueness of the developed nano-matrices of polyesteramide blends is that their mechanical strength is 3-fold higher than that of the nano-matrices of poly(L-lactide), which is one of the essential features of these nano-matrices to be used as a biomaterial for biomedical applications.

Nanobased intravenous and transdermal drug delivery systems - Gundloori, Rathna V. N.; Singam, Amarnath; Killi, Naresh (Applications of Targeted Nano Drugs and Delivery Systems, 2019)
In this chapter we bring in the collective information about intravenous and transdermal nano drug delivery systems (DDSs), which include different kinds of constituents used for the design of nano DDSs, their various forms, methods, and characterization of nanoformulations.

PEGylated ethyl cellulose micelles as a nanocarrier for drug delivery - Singam, Amarnath; Killi, Naresh; Patel, Pratikshkumar R.; Gundloori, Rathna V. N. (RSC Advances, 2021)
Natural polymers provide a better alternative to synthetic polymers in the domain of drug delivery systems (DDSs) because of their renewability, biocompatibility, and low immunogenicity; therefore, they are being studied for the development of bulk/nanoformulations. Likewise, current methods for engineering natural polymers into micelles are in their infancy, and in-depth studies are required using natural polymers as controlled DDSs. Accordingly, in our present study, a new micellar DDS was synthesized using ethyl cellulose (EC) grafted with polyethylene glycol (PEG); it was characterized, its properties, cell toxicity, and hemocompatibility were evaluated, and its drug release kinetics were demonstrated using doxorubicin (DOX) as a model drug. Briefly, EC was grafted with PEG to form the amphiphilic copolymers EC-PEG1 and EC-PEG2 with varying PEG concentrations, and nano-micelles were prepared with and without the drug (DOX) via a dialysis method; the critical micelle concentrations (CMCs) were recorded to be 0.03 mg mL(-1) and 0.00193 mg mL(-1) for EC-PEG1 and EC-PEG2, respectively. The physicochemical properties of the respective nano-micelles were evaluated via various characterization techniques. The morphologies of the nano-micelles were analyzed via transmission electron microscopy (TEM), and the average size of the nano-micelles was recorded to be similar to 80 nm. In vitro, drug release studies were done for 48 h, where 100% DOX release was recorded at pH 5.5 and 52% DOX release was recorded at pH 7.4 from the micelles. In addition, cytotoxicity studies suggested that DOX-loaded micelles were potent in killing MDA-MB-231 and MCF-7 cancer cells, and the blank micelles were non-toxic toward cancerous and normal cells. A cellular uptake study via fluorescence microscopy indicated the internalization of DOX-loaded micelles by cancer cells, delivering the DOX into the cellular compartments. Based on these studies, we concluded that the developed material should be studied further via in vivo studies to understand its potential as a controlled DDS to treat cancer.

Bioinspired hyaluronic acid based nanofibers immobilized with 3, 4-difluorobenzylidene curcumin for treating bacterial infections - Patel, Pratikshkumar R.; Singam, Amarnath; Iyer, Arun K.; Gundloori, Rathna Venkata Naga (Journal of Drug Delivery Science and Technology, 2022)
Curcumin (Cur) is a natural polyphenol with multifaceted pharmacological functions, exploited extensively for biomedical applications. Traditionally curcumin is being used as an antimicrobial agent. However, to improvise the pharmacological properties, it is being modified synthetically. One of such modified Cur is 3, 4- difluorobenzylidene curcumin (CDF) which is aimed for enhancing the anti-cancer properties. Though there are reports on the studies of anti-cancer properties involving CDF, the anti-bacterial property is yet to be demonstrated. Accordingly, in our studies, we prepared bioinspired hyaluronic acid blends immobilized with CDF and fabricated non-woven nanofiber mats. These nanofiber mats were characterized and demonstrated in vitro cell culture studies, which involved cell viability, hemolysis, anti-bacterial and cell scratch assay to understand their efficacy in treating bacteria. The molecular docking studies of CDF and Cur were performed on the dihydrofolate reductase (DHFR) enzyme receptor, which is an essential protein of S.auerus (Staphylococcus aureus). The results of MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) assay, and hemolysis of the respective nanofiber mats with Cur and CDF showed non-toxicity and were compatible with blood cells. Further, the cell proliferation and adherence recorded >60% fibroblast cells for the nanofiber mats. The anti-bacterial property of Cur and CDF was similar. The in vitro release studies for the respective Cur and CDF loaded nanofiber mats recorded a release of 25 and 37%, respectively. From these studies, we concluded that the CDF sustained its antibacterial property in addition to the improved anti-cancer property; hence CDF being synergetic, it will have a better scope in cancer therapy.
Keywords: anti-bacterial; curcumin; nanofibers; tissue engineering; wound Healing

Blend of neem oil based polyesteramide as magnetic nanofiber mat for efficient cancer therapy - Patel, Pratikshkumar R.; Singam, Amarnath; Dadwal, Arun; Gundloori, Rathna Venkata Naga (Journal of Drug Delivery Science and Technology, 2022)
Stearic acid-coated magnetic nanoparticles (SMN) and FU (5-Fluorouracil) were immobilized in the blends of neem oil-based polyesteramide and fabricated as nanofiber mat (NM) for controlled release of FU under the influence of an external magnetic field for targeted drug delivery to treat cancer efficiently. Analyzed the surface morphology of the fibers using E-SEM, it was observed that the fibers were smooth with the diameter ranging from 250 to 450 nm. TEM studies showed the uniform distribution of SMN in the nanofibers. The physico-chemical properties of NM and raw materials were analyzed using FTIR, TGA, and XRD. The results suggested that the polymers were well blended. In-vitro FU release studies of the NMs recorded a significant difference in the cumulative percentage of FU release from SMN-NMs. The SMN-NMs released 95% of FU in 4 h, whereas, NMs released 83% of FU in 24 h. The cell viability assay for the NM was evaluated in the L929 mouse fibroblast cells, where >75% of cells were viable. The hemolysis assay for the developed SMN-NF showed <5% of hemolysis, which indicated the NMs were safe for application. The anti-cancer activity of FU loaded SMN-NF was analyzed in the MCF-7 cancer cell line, which recorded more than 50% cell death within 24 h. From SQUID analysis, we found that the 10% SMN were superparamagnetic in nature, the magnetization at 30 kOe was observed to be 4.3 emu/g. Based on the in vitro results, we concluded that the developed SMN-NMs are recommended for in vivo studies to understand their efficacy for the targeted drug delivery to treat cancer.
Keywords: 5-Fluorouracil; drug release; electrospinning; Magnetic nanoparticles; nanofibers; Stearic acid

Combinatorial therapy using RNAi and curcumin nano-architectures regresses tumors in breast and colon cancer models - Kumar, Aviral; Singam, Amarnath; Swaminathan, Guruprasadh; Killi, Naresh; Tangudu, Naveen Kumar; Jose, Jedy; Gundloori, Rathna V. N.; Kumar, Lekha Dinesh (Nanoscale, 2022)
Cancer is a debilitating disease and one of the leading causes of death in the world. In spite of the current clinical management being dependent on applying robust pathological variables and well-defined therapeutic strategies, there is an imminent need for novel and targeted therapies with least side effects. RNA interference (RNAi) has gained attention due to its precise potential for targeting multiple genes involved in cancer progression. Nanoparticles with their enhanced permeability and retention (EPR) effect have been found to overcome the limitations of RNAi-based therapies. With their high transportation capacity, nanocarriers can target RNAi molecules to tumor tissues and protect them from enzymatic degradation. Accumulating evidence has shown that tyrosine kinase Ephb4 is overexpressed in various cancers. Therefore, we report here the development and pre-clinical validation of curcumin-chitosan-loaded: eudragit-coated nanocomposites conjugated with Ephb4 shRNA as a feasible bio-drug to suppress breast and colon cancers. The proposed bio-drug is non-toxic and bio-compatible with a higher uptake efficiency and through our experimental results we have demonstrated the effective site-specific delivery of this biodrug and the successfull silencing of their respective target genes in vivo in autochthonous knockout models of breast and colon cancer. While mammary tumors showed a considerable decrease in size, oral administration of the biodrug conjugate to Apc knockout colon models prolonged the animal survival period by six months. Hence, this study has provided empirical proof that the combinatorial approach involving RNA interference and nanotechnology is a promising alliance for next-generation cancer therapeutics.